Multifunctional Landscapes Science Program Technical Report Under Collaborative Research Agreement No. ILRI–RECONCILE CRA 1/2025 - Mukalo, Irene Aloo; Okoth, Joshua; Nganga, Irene (International Livestock Research Institute, 2025)
This report presents the implementation progress under the CRA-supported Multifunctional Landscapes Science Program for the period January to September 2025. During these nine months, RECONCILE advanced collaborative action across Baringo and Wajir Counties in Kenya, complementing regional learning and policy processes convened under CGIAR’s SPARC and AICCRA frameworks. The work reflected an integrated approach that combined evidence generation, institutional strengthening, and community-driven innovation to address the twin challenges of climate resilience and rangeland governance.